Higher order structures of Adalimumab, Infliximab and their complexes with TNFα revealed by electron microscopy. (14th November 2017) - Tran, Bich Ngoc; Chan, Siew Leong; Ng, Chloe; Shi, Jian; Correia, Ivan; Radziejewski, Czeslaw; Matsudaira, Paul
Abstract: Adalimumab and Infliximab are recombinant IgG1 monoclonal antibodies (mAbs) that bind and neutralize human tumor necrosis factor alpha (TNFα). TNFα forms a stable homotrimer with unique surface‐exposed sites for Adalimumab, Infliximab, and TNF receptor binding. Here, we report the structures of Adalimumab‐TNFα and Infliximab‐TNFα complexes modeled from negative stain EM and cryo‐EM images. EM images reveal complex structures consisting of 1:1, 1:2, 2:2, and 3:2 complexes of Adalimumab‐TNFα and Infliximab‐TNFα. The 2:2 complex structures of Adalimumab‐TNFα and Infliximab‐TNFα show diamond‐shaped profiles and the 2D class averages reveal distinct orientations of the Fab domains, indicating different binding modes by Adalimumab and Infliximab to TNFα. After separation by size exclusion chromatography and analysis by negative stain EM, the 3:2 complexes of Adalimumab‐TNFα or Infliximab‐TNFα complexes are more complicated but retain features recognized in the 2:2 complexes. Preliminary cryo‐EM analysis of 3:2 Adalimumab‐TNFα complex generated a low‐resolution density consistent with a TNFα trimer bound with three Fab domains from three individual antibody molecules, while each antibody molecule binds to two molecules of TNFα trimer. The Fc domains are not visible in the reconstruction. These results show the two mAbs form structurally distinct complexes with TNFα.